Outage Capacity of MIMO Poisson Fading Channels - Chakraborty, K.; Dey, S.; Franceschetti, M. (IEEE transactions on information theory, 2008)
The information outage probability of a shot-noise limited direct detection multiple-input-multiple-output (MIMO) optical channel subject to block fading is considered. Information is transmitted over this channel by modulating the intensity of a number of optical signals, one corresponding to each transmit aperture, and individual photon arrivals are observed at multiple receive photodetector apertures. The transmitted signals undergo multiplicative fading. The fading occurs in coherence intervals of fixed duration in each of which the channel fade matrix remains constant, and changes across successive such intervals in an independent and identically distributed fashion. The transmitter and the receiver are assumed to be provided with perfect channel state information (CSI). An optimization formulation for the outage probability problem is outlined and an exact characterization of the optimal average conditional duty cycles is provided.